2018
DOI: 10.1111/eea.12708
|View full text |Cite|
|
Sign up to set email alerts
|

Nutrient declines in overwintering Halyomorpha halys populations

Abstract: Brown marmorated stink bug, Halyomorpha halys (St al) (Hemiptera: Pentatomidae), has become a major pest for agricultural growers since it arrived in the USA and Europe. To better understand the energetic requirements of overwintering, dispersal, and reproduction of this invasive pest, we monitored the weight, egg load, lipid, glycogen, and sugar levels of adult H. halys populations in western Oregon, USA, over 2 years. In the first study, overwintering H. halys collected monthly from inside shelters exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…First, an explanation for these fluctuations is that it reflects the generational change in the population dynamics. As the overwintered generation of adults expend their energy in summer, they later die off in July/August upon which the newly emerging adults are often sampled with higher energetic reserves [ 12 ]. Secondly, another explanation for the fluctuations in nutrient levels could be the quality of food available and adult movement at different times of the summer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, an explanation for these fluctuations is that it reflects the generational change in the population dynamics. As the overwintered generation of adults expend their energy in summer, they later die off in July/August upon which the newly emerging adults are often sampled with higher energetic reserves [ 12 ]. Secondly, another explanation for the fluctuations in nutrient levels could be the quality of food available and adult movement at different times of the summer.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the energetic reserves of field-collected adults has revealed that extensive nutrient depletion occurs during overwintering. In spring, emerged BMSB adults have lower glycogen and sugar reserves than concurrently overwintering BMSB [ 12 ]. Furthermore, overwintering adults exhibit a 12–25% decline in lipid, a 48–70% decline in glycogen and a 54–79% decline in sugar levels from October–June [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the fall search for harborage, H. halys may leave their harborage and become active in homes through winter and spring, likely in response to poor nutritional state (Funayama 2012, Skillman et al 2018. During active periods, some become trapped and die in window frames, light fixtures, and ventilation systems.…”
mentioning
confidence: 99%
“…They crawl around the exteriors while searching for entry points and may quickly enter when doors and windows are opened. In spring, they exit, triggered at least in part by the depletion of their fat bodies (Skillman et al 2018). Throughout the colder months, individuals may exit their hiding places and move around indoors.…”
mentioning
confidence: 99%